Post-transplant cyclophosphamide after matched sibling, unrelated and haploidentical donor transplants in patients with acute myeloid leukemia: a comparative study of the ALWP EBMT - Jaime Sanz; Jacques-Emmanuel Galimard; Myriam Labopin; Boris Afanasyev; Emanuele Angelucci; Fabio Ciceri; Didier Blaise; Jan J. Cornelissen; Ellen Meijer; J. L. Diez-Martin; Yener Koc; Montserrat Rovira; et al. (Journal of Hematology & Oncology, 2020)
Abstract Background The use of post-transplant cyclophosphamide (PTCy) is highly effective in preventing graft-versus-host disease (GVHD) in the haploidentical (Haplo) transplant setting and is being increasingly used in matched sibling (MSD) and matched unrelated (MUD) transplants. There is no information on the impact of donor types using homogeneous prophylaxis with PTCy. Methods We retrospectively compared outcomes of adult patients with acute myeloid leukemia (AML) in first complete remission (CR1) who received a first allogeneic stem cell transplantation (SCT) with PTCy as GVHD prophylaxis from MSD (n = 215), MUD (n = 235), and Haplo (n = 789) donors registered in the EBMT database between 2010 and 2017. Results The median follow-up was 2 years. Haplo-SCT carried a significantly increased risk of acute grade II–IV GVHD (HR 1.6; 95% CI 1.1–2.4) and NRM (HR 2.6; 95% CI 1.5–4.5) but a lower risk of relapse (HR 0.7; 95% CI 0.5–0.9) that translated to no differences in LFS (HR 1.1; 95% CI 0.8–1.4) or GVHD/relapse-free survival (HR 1; 95% CI 0.8–1.3). Interestingly, the use of peripheral blood was associated with an increased risk of acute (HR 1.9; 95% CI 1.4–2.6) and chronic GVHD (HR 1.7; 95% CI 1.2–2.4) but a lower risk of relapse (HR 0.7; 95% CI 0.5–0.9). Conclusions The use of PTCy in patients with AML in CR1 receiving SCT from MSD, MUD, and Haplo is safe and effective. Haplo-SCT had increased risk of acute GVHD and NRM and lower relapse incidence but no significant difference in survival.